PENGEMBANGAN MEDIA KOTAK PINTER AKSARA JAWA (PIRAWA) PADA MATA PELAJARAN BAHASA JAWA KELAS IV SD NEGERI GONDANG 03 KABUPATEN BATANG - Sinta Dina Afiana; Mira Azizah; Ervina Eka Subekti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The problem was found that the learning media was limited, the learning method was only lectures and assignments, the teacher had not used creative learning media which resulted in students not being enthusiastic and students' learning motivation low. The purposes of this research are 1) Knowing the procedure for developing Pirawa Box media, 2) Knowing the feasibility level of Pirawa Box media, 3) Knowing the practicality of Pirawa Box media. This study uses the Research and Development (RnD) method. Data collection techniques using interviews and questionnaires. Data were analyzed using qualitative descriptive and quantitative descriptive. The results showed that the Kotak Pirawa media was declared feasible with the analysis results from the media expert validation of 100% and the results of the material expert validation analysis of 95.7% very good category. The Pirawa Box media was stated to be practical with a percentage of 100% in the very good category. Through the results of the student response questionnaire analysis obtained a percentage of 99%. Based on the results of this study, the Pirawa Box media developed was declared feasible and practical to use in the learning process.